Very long-term outcomes of patients undergoing catheter ablation of atrial fibrillation: a systematic review and meta-analysis. (3rd October 2022) - Ngo, L; Lee, W; Elwashahy, M; Arumugam, P; Ranasinghe, I
Abstract: Background: The efficacy of catheter ablation of atrial fibrillation (AF) is reported to stabilise at 5-year, but most studies report up to 3-year-outcomes only. Objective: To perform a systematic review and meta-analysis of outcomes at 5-years following AF ablation. Methods: We searched PubMed and Embase for studies reporting on ≥5-year outcomes following AF ablation, including freedom from atrial arrhythmia, all-cause death, stroke, and major bleeding. All meta-analyses were performed using the "meta" package in R with pooled incidence calculated using log transformation. Results: Among 5, 764 studies screened, 58 (n=41, 344 patients) were included for analysis. The pooled mean age was 60.3y, 68.7% male, 78.4% paroxysmal AF, and radiofrequency was the most common ablation energy (72.4%). Most (51.5%) patients had hypertension, but the pooled rates of other comorbidities were low (heart failure: 9.0%, coronary artery disease: 12.8%, diabetes: 11.0%, and previous stroke: 8.5%). Pooled incidence of freedom from atrial arrhythmia at 5-years was 47.6% (95% CI 43.8%-51.6%, I 2 =98.4%) after a single procedure and increased to 64.3% (95% CI 59.6%-69.3%, I 2 =98.3%) after multiple procedures (Figure 1). The incidence was higher among patients with paroxysmal compared with non paroxysmal AF (55.9% vs. 28.7% and 82.2% vs. 47.6% after single and multiple procedures respectively). Retrospective studies reported slightly higher incidence of arrhythmia freedom (single procedure: 51.2% vs. 46.7%; multiple procedures: 66.9% vs. 61.9%) than did prospective studies. Few studies reported outcomes other than atrial arrhythmia free survival at 5-years (n=14) and incidences of these outcomes could only be pooled for multiple procedures. Pooled incidences of death, stroke, and major bleeding at 5-years were 8.0% (95% CI 4.2%-15.2%, I 2 =95.8%), 2.3% (95% CI 1.4%-3.6%, I 2 =72.9%), and 1.1% (95% CI 0.6%-1.8%, I 2 =32.5%), respectively (Figure 2). Conclusion: At five-years, only up to 65% of patients undergoing AF ablations remained free from atrial arrhythmia although there was significant heterogeneity among individual studies. Encouragingly, these patients had low risk of dying, experiencing a stroke or major bleeding (all incidences<10%). Funding Acknowledgement: Type of funding sources: None.